1990
DOI: 10.1152/ajprenal.1990.259.3.f438
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor accelerates renal repair in mercuric chloride nephrotoxicity

Abstract: Repair and recovery of ischemic or nephrotoxic acute renal failure (ARF) are dependent upon renal tubule cell regeneration. Because epidermal growth factor (EGF) is a potent growth promoter to renal tubule cells, experiments were undertaken to assess the effects of exogenous administration of EGF during the recovery phase of HgCl2-induced ARF. Rats were administered HgCl2 (5 mg/kg sc), and [3H]thymidine incorporation into renal tissue and blood urea nitrogen (BUN) and serum creatinine concentrations were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 0 publications
3
66
1
1
Order By: Relevance
“…In the post-ischemic kidney, a significant increase in HB-EGF mRNA levels was observed within 1 h of reperfusion. Expression of HB-EGF mRNA remained elevated at 6 h of reperfusion (8.0+2.0-fold of that in the contralateral kidney; n = 5; P < 0.05) and in some experiments was still elevated at 24 and 48 h. Acute injury and subsequent regeneration of tubular epithelial cells are also induced by a variety of nephrotoxins, including mercuric chloride (1,4). Mercuric chloride administration induced expression of HB-EGF mRNA in the kidney within 5 h (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In the post-ischemic kidney, a significant increase in HB-EGF mRNA levels was observed within 1 h of reperfusion. Expression of HB-EGF mRNA remained elevated at 6 h of reperfusion (8.0+2.0-fold of that in the contralateral kidney; n = 5; P < 0.05) and in some experiments was still elevated at 24 and 48 h. Acute injury and subsequent regeneration of tubular epithelial cells are also induced by a variety of nephrotoxins, including mercuric chloride (1,4). Mercuric chloride administration induced expression of HB-EGF mRNA in the kidney within 5 h (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Retrograde aortic perfusion with phosphate buffered saline was performed to remove blood from the kidney. In separate experiments, renal tubular injury was induced by a subcutaneous administration of mercuric chloride (5 mg/kg body wt) 5 h before time of killing (4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infusion ofadenine nucleotides or EGF can speed recovery of injured kidney tubules in rats with experimental acute renal failure (7,(54)(55)(56). The results indicated that EGF was as potent as adenosine and adenine nucleotides, basic FGF and IGF-I were much less stimulatory, and PDGF, IGF-II, and acidic FGF had no effect.…”
Section: Discussionmentioning
confidence: 99%
“…These growth factors include epidermal growth factor, hepatocyte growth factor (HGF), 1 and insulin-like growth factor-I (9-13). A number of studies have investigated the potential role of EGF and/or the EGF family of growth factors in renal injury (9)(10)(11)14). EGF production in the normal adult mammalian kidney has been localized to the thick ascending limb/distal convoluted tubule (15).…”
Section: Introductionmentioning
confidence: 99%